PERSEPSI SISWA TERHADAP GAMIFIKASI QUIZIZZ DALAM PEMBELAJARAN PPKN DI SMKN 1 SERANG - Januar, Muhamad Caesar (Academy of Education Journal, 2023)
This study aims to determine the perceptions of students towards the utilazation of quizizz educational game based learning media in class 12st of the 1 Vocational High School in Serang City. This study used a survey research method with 67 respondent, and was selected randomly through random sampling technique.based on the results of the study, it shows that students consider quizizz educational game-based learning media as media that is easy to use, fun to use, that can increase learning effectiveness, media that can increase motivation and involve activeness in the learning process.as or the weaknesses, that are a problem in using quizizz educational game media according to students, namely relate to internet connections that must be stable so that they require a good network connection.